Interannual Variability of Climatology and Tropical Cyclone Tracks in North Atlantic and Western North Pacific - Yan, Tingzhuang (2006)
The spatial-temporal variability of tropical cyclone tracks and their possible association with tropical cyclone landfall frequency along the United States East Coast and China East Coast are studied using Principle Component Analysis of tropical cyclone Track Density Function (TDF). Results show that North Atlantic (NA) hurricane TDF is strongly modulated by El Niño-South Oscillation, the tropical Atlantic SST dipole Mode (DM), North Atlantic Oscillation and Arctic Oscillation. Dominant Modes of Western North Pacific (WNP) typhoon TDF demonstrate strong correlation with spring and winter snow cover (SC) over the Qinghai and Tibetan Plateau (QTP). Results provide a foundation for the construction of statistical models, which project the annual number of tropical cyclone landfall along the East Coast of the United States and the coast of China. Analysis for 1990 and 2004 NA hurricane seasons revealed that the substantial variability of tropical Atlantic SST DM is a dominate factor affecting the hurricane track patterns. Study for 1978 and 2001 typhoon cases in the WNP demonstrated that the QTP SC was responsible for the differentiation in the number of landfall typhoon events in the WNP. A schematic diagram was proposed to illustrate the linkage between the DM and the NA hurricane track patterns. Accumulated gain or deficit in the surface radiation associated with the QTP SC imposes a long memory in the East Asian climate system. Variations in heat budget change the large-scale zonal circulation and further modulate the seasonal position and strength of East Asian subtropical high. A possible physical link to connect the QTP snow cover and the WNP typhoon track patterns was therefore proposed.